2021
DOI: 10.3389/fcvm.2021.718055
|View full text |Cite
|
Sign up to set email alerts
|

rGO/Silk Fibroin-Modified Nanofibrous Patches Prevent Ventricular Remodeling via Yap/Taz-TGFβ1/Smads Signaling After Myocardial Infarction in Rats

Abstract: Objective: After acute myocardial infarction (AMI), the loss of cardiomyocytes and dysregulation of extracellular matrix homeostasis results in impaired cardiac function and eventually heart failure. Cardiac patches have emerged as a potential therapeutic strategy for AMI. In this study, we fabricated and produced reduced graphene oxide (rGO)/silk fibroin-modified nanofibrous biomaterials as a cardiac patch to repair rat heart tissue after AMI and investigated the potential role of rGO/silk patch on reducing m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Moreover, to extend the duration of pharmaceutical drug delivery, Chen et al encapsulated, the fluorine substituent of TAZ-12, TT-10, into polylactic-co-glycolic acid nanoparticles, which effectively activated the cell cycle of hiPSC-CMs and inhibit apoptosis by upregulating YAP 545 . Feng et al implanted reduced graphene oxide (rGO)/silk fibroinmodified nanofibrous biomaterials into the heart, showing a direct effect on preventing rat ventricular remodeling via YAP/ TAZ 546 . Due to the regenerative properties of stem cells, stem cell therapy has been engaged to repair injured heart tissues 547 .…”
Section: Hippo Signaling Pathway In MImentioning
confidence: 99%
“…Moreover, to extend the duration of pharmaceutical drug delivery, Chen et al encapsulated, the fluorine substituent of TAZ-12, TT-10, into polylactic-co-glycolic acid nanoparticles, which effectively activated the cell cycle of hiPSC-CMs and inhibit apoptosis by upregulating YAP 545 . Feng et al implanted reduced graphene oxide (rGO)/silk fibroinmodified nanofibrous biomaterials into the heart, showing a direct effect on preventing rat ventricular remodeling via YAP/ TAZ 546 . Due to the regenerative properties of stem cells, stem cell therapy has been engaged to repair injured heart tissues 547 .…”
Section: Hippo Signaling Pathway In MImentioning
confidence: 99%
“…Interestingly, biomaterial-based substrates can also serve as patches to deliver therapeutic molecules and provide mechanical support. Silk fibroin (SF), a natural biomacromolecule, has attracted wide interest in tissue engineering due to its biocompatibility, biodegradability, morphologic flexibility, and a number of tangible mechanical properties [ 30 ]. Recently, SF has been demonstrated as a potential alternative to induce the reprogramming and conversion of rat quiescent ventricular cardiomyocytes to pacemaker cardiomyocytes without affecting transcription factors [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the MI animal model, studies showed that reduced graphene oxide (rGO)/silk yields the ability to promote cardiomyocyte structure formation and functions because it can mimic the natural cardiac ECM and provide mechanical support for recovery after MI (181). Further, rGO/silk remarkably reduces the expression of the canonical TGF-b/Smads signaling pathway and YAP/TAZ in the infarcted heart (182).…”
Section: The Impact Of Adipose Tissue Under Mechanical Changes During...mentioning
confidence: 90%